Kontruksi Deradikalisasi Dakwah Islam: Peran Nahdlatul Ulama dalam Upaya Melawan Radikalisme di Indonesia - Zakariya, A. Fahmi; Iqbal, Mohammad; Nafiuddin, Agus (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2024)
Radicalism is an important problem for Indonesian Muslims today. The involvement of various leading sectors in dealing with the problem of radicalism (deradicalization) is highly expected. The Indonesian government through the National Counterterrorism Agency (BNPT) is trying to take strategic steps in carrying out the deradicalization movement, one of which is by collaborating with the Islamic organization Nahdlatul Ulama (NU). Nahdlatul Ulama as a social organization with moderate views, as well as having a strong and broad organizational network that can reach the grassroots is expected to be very strategic in countering the spread of radical and extremist views in Indonesia. The deradicalization concept applied by Nahdlatul Ulama is carried out in a persuasive way by prioritizing a humanist approach in building dialogue within the internal circles of Islamic society. For example, through the proselytizing movement of NU clerics and kiai, through the pesantren network, through scientific studies such as bahtsul masail, NU online da'wah media, and by fortifying Aswaja-based NU educational institutions (Ahlussunah wal Jamaah).